Preclinical anti‐angiogenic and anti‐cancer activities of BAY1143269 in glioblastoma via targeting oncogenic protein expression. Issue 4 (7th July 2022) - Wan, Weifeng; Zhang, Xin; Huang, Changren; Chen, Ligang; Yang, Xiaobo; Bao, Kunyang; Peng, Tangming
Abstract: Glioblastoma angiogenesis is critical for tumor growth, making it an appealing target for treatment development. BAY1143269 is a novel inhibitor of mitogen‐activated protein kinase interacting serine/threonine‐protein kinase 1 (MKN1) and has potent anti‐cancer activity. We identified BAY1143269 as an angiogenesis inhibitor, by in vitro and in vivo glioblastoma angiogenesis models. BAY1143269 inhibited the capillary network formation of glioblastoma microvascular endothelial cells (GMECs), particularly the early stage of tubular structure formation. It also inhibited migration and proliferation, and induced apoptosis of GMECs isolated from glioblastoma patients. We found that BAY1143269 acted on GMECs by suppressing the eukaryotic translation initiation factor 4E (eIF4E) and eIF4E‐mediated expression of oncogenic proteins, including those involved in cell cycle, epithelial‐mesenchymal transition (EMT), and pro‐survival. In addition, BAY1143269 suppressed eIF4E phosphorylation, inhibited proliferation, and induced apoptosis of glioblastoma cells. Interestingly, it reduced vascular endothelial growth factor (VEGF) level in tumor cells and culturing medium, demonstrating the inhibitory effect of BAY1143269 on tumor proangiogenic microenvironment. We finally challenged BAY1143269 on the glioblastoma xenograft mice model and observed a significant tumor growth reduction without toxicity in mice receiving oral BAY1143269. Immunoblotting analysis demonstrated significantly less phosphorylated‐eIF4E (p‐eIF4E), cluster of differentiation 31 (CD31) (microvascular endothelial cell marker), and VEGF in tumors from drug‐treated mice. In summary, the inhibition of glioblastoma angiogenesis with BAY1143269 may provide an alternative approach for anti‐glioblastoma therapy. Abstract : BAY1143269 is a novel inhibitor of mitogen‐activated protein kinase interacting serine/threonine‐ protein kinase I MKNI) and has potent anti‐cancer activity. We identified BAY1143269 as an angiogenesis inhibitor, by in vitro and in vivo glioblastoma angiogenesis models.,